Lightweight design based on automotive drive axle housing - Yingshuai Liu; Chenxing Liu; Jianwei Tan; Yunli He (PLoS ONE, 2025)
To address the limitations in the cruising range and improve the overall efficiency of Pure Electric Vehicles (PEVs), this study focuses on the lightweight design of PEV drive axles. Aligning with the current trend toward lightweight and integrated development in electric vehicles, the research is based on the concept of an integrated electric drive axle housing. A three-dimensional model of the electric vehicle axle was developed using three-dimensional modeling software(3D modeling software), taking into account the working principles and load characteristics of the electric drive axle. Subsequently, Finite Element Analysis (FEA) was performed using finite element analysis software to evaluate the stiffness, strength, and modal characteristics of the integrated electric drive axle housing. The study analyzed stress distribution, deformation patterns, and natural frequency ranges under various operating conditions. Based on the FEA results, the axle housing structure was optimized by reducing the wall thickness and modifying the material of components subjected to lower stress levels, with the goal of minimizing mass. The optimal solution involved adjusting the housing thickness to achieve a more uniform and efficient thickness distribution, thereby meeting the lightweight design objectives. Simulation verification of the optimized axle structure confirmed that the weight reduction was achieved without compromising the required strength and stiffness. The findings demonstrate that, while ensuring safety, the optimized axle structure achieved a 12% reduction in weight. This study provides a feasible solution and a solid theoretical foundation for advancing the development of lightweight electric vehicles.